Minocycline modulates microglia polarization in ischemia-reperfusion model of retinal degeneration and induces neuroprotection - Ahmed, Amel (Sci Rep, 2017)
Retinal ischemia-reperfusion (IR) injury causes irreversible loss of neurons and ultimately leads to permanent visual impairment and blindness. The cellular response under this pathological retinal condition is less clear. Using genetically modified mice, we systematically examined the behavior of microglia/macrophages after injury. We show that IR leads to activation of microglia/macrophages indicated by migration and proliferation of resident microglia and recruitment of circulating monocytes. IR-induced microglia/macrophages associate with apoptotic retinal neurons. Very interestingly, neuron loss can be mitigated by minocycline treatment. Minocycline induces Il4 expression and M2 polarization of microglia/macrophages. IL4 neutralization dampens minocycline-induced M2 polarization and neuroprotection. Given a well-established safety profile as an antibiotic, our results provide a rationale for using minocycline as a therapeutic agent for treating ischemic retinal degeneration.